CORPORATE SOCIAL RESPONSIBILITY AS A GATEWAY TO SUSTAINABLE DEVELOPMENT IN NIGERIA - Orji, Alexander Onyekachi (My University, 2009)
The objective of this study was to examine and analyze how corporate social responsibility of multinational firms, small and medium-sized enterprises would serve as a gateway towards sustainable development in Nigeria. The research problem, in this study, was to identify the expected corporate roles from these firms towards sustainable development in the case country. The research methodology was based lightly on primary data and heavily based on secondary data i.e. written documents and internet. The study created a new framework for analyzing the development situation in the case country when all the corporate roles are fully implemented. The result at the end of this work was that sustainable development of Nigeria could only be achieved if all the corporate bodies operating within the nation should carry out their economic, socio-cultural and environmental roles to the core without any bias mind.
Keywords: corporate social responsibility; sustainable development; multinational corporations; stakeholder theory; Nigeria.; fi=Tuotantotalous|en=Industrial Management|